Soil Health, Conservation, and U.S. Agriculture Policy: Using System Modeling to Create Policy Scenarios for Improved Soil Health in New York - Fanous, Jamie. (2018)
Abstract: Maintaining soil health is pertinent to environmental, social, and economic sustainability. Soil health ensures human health, well-being of ecosystems, agriculture efficiency, and security from a shifting climate. However, the adoption of soil health practices requires adjustments from agricultural norms towards conservation strategies. This shift requires technical and economic support of farmers to ensure success. This study models the current federal strategies to promote conservation agriculture(CA) practices, and suggests adjustments in priorities to guarantee improvements in U.S. agricultural soils. This paper illustrates how supporting farmers to adopt CA practices is arguably the most cost-effective strategy to improve land management, mitigate climate change, ensure food security, and certify overall sustainability. Utilizing the current EQIP allocation framework, CA adoption across all New York could be attained within 10 years costing roughly $87 million dollars. These estimates allow for broader conversation and opportunities for U.S. government involvement in implementation of soil health initiatives.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Ann Rappaport, and Christian Peters.; Keyword: Agriculture.